Impact of COVID-19 on the mental health of medical students: A meta-analysis - Santabárbara Serrano, Javier; Bueno Notivol, Juan (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The aim of this work was to estimate the overall proportion of anxiety in medical students during the COVID-19 pandemic. A systematic search of articles published up to January 6, 2021 in Medline reporting prevalence of anxiety (according to GAD-7)in medical students during the COVID-19 pandemic was performed. Ten studieswere included in the meta-analysis, yielding an estimated overall prevalence ofanxiety in medical students of 42. This finding suggests the need to assess anxioussymptomatology among medical students during the COVID-19 pandemic andestablish appropriate psychological support programs.